2001
DOI: 10.1038/35054555
|View full text |Cite
|
Sign up to set email alerts
|

Horsetails and ferns are a monophyletic group and the closest living relatives to seed plants

Abstract: Most of the 470-million-year history of plants on land belongs to bryophytes, pteridophytes and gymnosperms, which eventually yielded to the ecological dominance by angiosperms 90 Myr ago. Our knowledge of angiosperm phylogeny, particularly the branching order of the earliest lineages, has recently been increased by the concurrence of multigene sequence analyses. However, reconstructing relationships for all the main lineages of vascular plants that diverged since the Devonian period has remained a challenge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
480
4
24

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(545 citation statements)
references
References 26 publications
37
480
4
24
Order By: Relevance
“…We also evaluate variation caused by method of estimation and calibration point. We estimate the ages, with confidence intervals, of major clades of tracheophytes, using (i) a tree based on four genes and morphology (21), (ii) data from four genes singly and combined, and (iii) multiple calibration points representing well-substantiated dates in the fossil record. We also test for rate constancy among lineages and heterogeneity of rates among genes and codon positions in protein-coding genes and evaluate sensitivity of age estimates to branch lengths inferred by maximum parsimony (MP) and maximum likelihood (ML), the effectiveness of NPRS relative to an assumption of rate constancy, and the correspondence of molecular-based estimates to the fossil record.…”
mentioning
confidence: 99%
“…We also evaluate variation caused by method of estimation and calibration point. We estimate the ages, with confidence intervals, of major clades of tracheophytes, using (i) a tree based on four genes and morphology (21), (ii) data from four genes singly and combined, and (iii) multiple calibration points representing well-substantiated dates in the fossil record. We also test for rate constancy among lineages and heterogeneity of rates among genes and codon positions in protein-coding genes and evaluate sensitivity of age estimates to branch lengths inferred by maximum parsimony (MP) and maximum likelihood (ML), the effectiveness of NPRS relative to an assumption of rate constancy, and the correspondence of molecular-based estimates to the fossil record.…”
mentioning
confidence: 99%
“…One is EaChiA, the other is PrChiA. Pryer et al 32) showed that there are three monophyletic groups of extant vascular plants: seed plants, lycophytes, and ferns (seedless vascular plants without lycophytes). This refutes the notion that ferns are transitional evolutionary grades between bryophytes and seed plants.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Smith et al (2006), Hymenophyllaceae é monofilética e está constituída por nove gêneros, 600 espécies e dois grandes clados formados por espécies tricomanóides e himenofilóides (Pryer et al 2001, Smith et al 2006.…”
Section: Dicranopterisunclassified